The Effect of Slope Steepness on Soil Loss under Natural Rainfall Distribution - Ali, Mohd Fozi (2000)
Similar to most of the other developing countries, Malaysia is characterised by a rapid transformation of vast areas of rainforest and steep land into agricultural, settlement and development land. These activities in the developing countries, are however carried out in an in-ecological manner especially which has led to soil erosion. Soil erosion by water is a serious problem in tropical countries like Malaysia, particularly on steep land and in areas devoid of vegetative cover. The degree of slope steepness is one important factor among others affecting soil erosion. The effect of slope steepness on soil erosion study on Munchong series was conducted in Universiti Putra Malaysia, Serdang. Three experimental plots of 2m X 4m were constructed on three different slopes of 6°, 12° and 15o. An experimental determination of runoff volume and soil loss as a function of slope, were studied on bare plots using the "soil erosion gauge". Rainfall intensity influences both the rate and volume of runoff and significantly affected the amount of soil loss in different category of slopes. Runoff increased appreciably with increase of slope. The non-linear regression relationship between runoff and slope steepness can be expressed as RN = 46.38 (ST) 0.655 where RN is the amount of runoff (litre/ha) and ST is the slope steepness (degree). The amount of runoff will increase approximately 1.6 times as the degree of slope is doubled. Soil losses can be expected to increase with slope steepness as a result of respective increase in volume of surface runoff. The amount of soil erosion per unit area on Munchong series with 807 mm raindepth increased approximately 9.8 times as the degree of slope is doubled. The relationship between soil loss and steepness of slope could be represented by non-linear equation A= 0.003 (ST)3.292 where A is the weight of soil loss (ton/ha) and ST is the degree of slope steepness. Slope alone does not significantly influence the amount of sediment yield harvests. Soil loss was also caused by the interaction of several other factors such as rainfall, vegetation, soil properties and mechanical practices. It is difficult to evaluate the interaction of natural rainfall with other factors causing erosion, because of its variability from one location to another.